2022
DOI: 10.1371/journal.pone.0262196
|View full text |Cite
|
Sign up to set email alerts
|

The influence of role awareness, empathy induction and trait empathy on dictator game giving

Abstract: We ask how state empathy, trait empathy, and role awareness influence dictator game giving in a monetarily incentivized experiment. We manipulated two factors: role awareness (role certainty vs. role uncertainty) and state empathy induction (no empathy induction vs. empathy induction). Under role uncertainty, participants did not know their role as a dictator or a recipient when making their choices. State empathy was induced by asking the dictators to consider what the recipient would feel when learning about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…The lack of association between affective empathy and donation amount may seem surprising at first. However, some previous studies have also reported no association between induced empathy and generosity in a dictator game (e.g., Herne et al, 2022;Lönnqvist & Walkowitz, 2019). This suggests that the dictator game may be measuring a slightly different aspect of prosocial behavior than affective empathy, albeit one that does not seem to differ in horror fans.…”
Section: Discussionmentioning
confidence: 82%
“…The lack of association between affective empathy and donation amount may seem surprising at first. However, some previous studies have also reported no association between induced empathy and generosity in a dictator game (e.g., Herne et al, 2022;Lönnqvist & Walkowitz, 2019). This suggests that the dictator game may be measuring a slightly different aspect of prosocial behavior than affective empathy, albeit one that does not seem to differ in horror fans.…”
Section: Discussionmentioning
confidence: 82%
“…The predictive capacity of various sentiment analysis tools should be examined, dissecting the 'black box' to understand the mechanics of language's influence on decision-making. This will be fundamental for developing and testing a specific utility Schurter & Wilson [56] Dreber et al [55] Kettner & Ceccato [51] Kettner & Waichman [53] Walkowitz [57] Herne et al [58] Capraro & Vanzo [17] Bruttel & Stolley [54] Kuang & Bicchieri [24] Brañas-Garza [52] Antinyan et al [ Forest plot of the meta-analysis of the sentiment associated with altruistic behaviour across the studies. One study [49] gets dropped from the meta-analysis, because GPT-4 estimates the same sentiments in all four conditions, therefore the study-level regression does not estimate the standard error.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate coefficient and standard error at the study level using a linear regression, we need studies with at least three experimental conditions because a linear regression with two data points returns no standard error since there is only one line that passes through two distinct points. We collected 12 research articles with a total of 61 experimental conditions that satisfy this requirement [17,24,[49][50][51][52][53][54][55][56][57][58].…”
Section: A Meta-analysis Of Dictator Game Experimentsmentioning
confidence: 99%
“…This study directly investigated the impact of different TE components on online news belief, using participants' judgment of news believability as the primary measure. Given that affective empathy rather than cognitive empathy is more relevant to people's behaviors (such as prosocial behavior and moral decision making) [28][29][30], we propose Hypothesis 1: an individual's AE, rather than CE, would be more related to their belief in online news. Specifically, higher scores in AE would be associated with higher belief in online news.…”
Section: Trait Empathy and The Online News Beliefmentioning
confidence: 99%